Economic geography - "Kaur, Raninder" (Jaipur, 2006)
Economic geography focuses on the study of spatial aspects of economic activities on various scales. The distance to the city plays a significant role in economic decisions of firms while other factors such as access to the sea and the presence of raw materials like oil affects the economic conditions of countries. In today's world location and distribution of economic activities is much influenced by globalization. States and their borders play less significant role as many countries tend to eliminate the effects of borders and deepen the mutual cooperation of border regions that are often economically marginal and underdeveloped.
Keywords: Economic geography